Transport of Central American Fire Emissions to the U.S. Gulf Coast: Climatological Pathways and Impacts on Ozone and PM2.5. Issue 15 (14th August 2018) - Wang, Sing‐Chun; Wang, Yuxuan; Estes, Mark; Lei, Ruixue; Talbot, Robert; Zhu, Liye; Hou, Pei
Abstract: Fire emissions from Mexico and Central America are transported regularly to the U.S. Gulf Coast every spring under prevailing circulation patterns and affect U.S. air quality. Here we use a GEOS‐Chem passive tracer simulation to develop the climatology of transport pathways of fire emissions over a long‐term time period of April and May 2002–2015 and estimate their adverse air quality effects for urban areas along the Gulf Coast. A conceptual model is presented to describe the transport mechanisms, which involve southerly low‐level jets in the lower troposphere and warm conveyor belt in the middle troposphere. The warm conveyor belts and the southerly low‐level jets explain 31% and 69% of the interannual variability of the mid‐altitude (1.5–6 km) and low‐altitude events (0–1.5 km), respectively. Considering both transport and fire emissions, approximately 9% of the study period (59–88 days of 854 days) were identified as large pollution events during which Central American fire emissions adversely impacted surface air quality at several major urban centers along the Gulf Coast, including Houston and Corpus Christi in TX, New Orleans in LA, Mobile in AL, and Pensacola in FL. Compared to clean maritime flow from the Gulf of Mexico, these events were estimated to result in average enhancements of maximum daily average 8‐hr (MDA8) ozone and daily PM2.5 (fine particulate matter <2.5 μm in diameter) in the Gulf Coast cities of 3–12 ppbv and 2–5 μg/m 3, respectively. Only one ozone exceedance day (79 ppbv, on 18 May 2003) was found among the fire‐impact days for the Houston region. Key Points: Southerly low‐level jets and warm conveyor belts are the main mechanisms transporting Central American fire emissions to the United States Large transport events were identified, accounting for ~9% of the study period These large events increased daily MDA8 ozone and PM2.5 in Gulf Coast cities by 3–12 ppbv and 2–5 μg/m 3, respectively